Energy constrained max-min fair sharing resource allocation in mobile grid - Singh, Arjun; Ahmed, Gulrej; Chauhan, Surbhi (International Journal of Engineering and Technology, 2019)
In Mobile Grid Computing systems, the instinctive provisioning of services initially involves the discovery of mobile node. Resource allocation has been a great challenge for mobile grid environment. This paper presents an improved and efficient approach for optimized resource allocation. This Paper provides an energy efficient and effective solution to improve the efficiency of the grid. Proposed algorithm uses distance, bandwidth, CPU speed, and battery power as parameters. The detected power is applied to algorithm for a job scheduling algorithm. For the efficient resource allocation this paper is using a max-min algorithm with a job scheduling. These jobs are scheduled according to required power and available power. Using the described methods, the result shows power efficient and well maintained resource allocation for jobs sends to mobile grids.
Keywords: Energy Dissipation; Job Scheduling; Battery Power; MAX-MIN Algorithm.